1998
DOI: 10.1046/j.1432-1327.1998.2580744.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NF‐Y in transcriptional regulation of the phospholamban gene

Abstract: To understand the transcriptional regulation of the phospholamban gene, we analyzed a 5′-upstream region of the gene. Using a series of deletion constructs, we demonstrated that the region from Ϫ96 bp to Ϫ78 bp, containing the CCAAT sequence, is essential for transcription of this gene. This region specifically bound to nuclear proteins extracted from rat hearts, and gel-shift assays using competitive oligonucleotides, antibodies and recombinant proteins showed that this region binds to the NF-YA and NF-YB, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Two additional regions also show a marked conservation: an AT‐rich region (−217/−170) is approximately 70% conserved and the region between −169 and −134 shows 85% conservation. PLN promoter is a strong promoter, although all the transcriptional proteic factors still remain unknown [18]. Our experiments showed that the PLN −42 C<G mutation affects PLN promoter strength: PLN −42 C<G results in a 43% and 47% decrease of promoter activity compared to wild‐type PLN promoter in C6 and C2C12 cell lines, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Two additional regions also show a marked conservation: an AT‐rich region (−217/−170) is approximately 70% conserved and the region between −169 and −134 shows 85% conservation. PLN promoter is a strong promoter, although all the transcriptional proteic factors still remain unknown [18]. Our experiments showed that the PLN −42 C<G mutation affects PLN promoter strength: PLN −42 C<G results in a 43% and 47% decrease of promoter activity compared to wild‐type PLN promoter in C6 and C2C12 cell lines, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…These cell lines had been previously used in the study of the PLN promoter. C6 allows a high basal luciferase expression under the control of PLN promoter and C2C12 had been chosen for the study of PLN promoter activity in a muscular tissue without endogenous phospholamban expression [18,19]. Both C6 and C2C12 cell lines were cultured in Dulbecco's‐modified Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and antibiotic/antimicotic mix (Gibco.…”
Section: Methodsmentioning
confidence: 99%
“…The study identifies ZBTB20 as a novel regulator of PLN expression, adding to the existing knowledge of transcriptional regulation of PLN. Previous research has demonstrated the involvement of various transcriptional factors, including glucocorticoid nuclear receptor, 17 TRα1 (thyroid hormone receptor α1), 16 NF-YA (subunit A of nuclear factor Y), and NF-YB (subunit B of nuclear factor Y), 41 in the regulation of PLN at the transcriptional level. In cardiac myocytes, the expression of PLN is significantly decreased by T 3 , a process that is facilitated by TRα1 and involves the recruitment of histone-modifying enzymes associated with transcriptional silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Within the proximal promoter sequence for V9, we have identified a binding site for the nuclear transcription factor NF-Y. NF-Y can act on tissuerestricted promoters such as phospholamban (37) and the Na,K-adenosine triphosphatase ␣ 3 -subunit (38), even though binding sites for NF-Y (CCAAT-boxes) exist in many mammalian promoters, and NF-Y itself may be ubiquitously expressed (39). Clearly, promoter context is important in determining the specificity of gene expression (40).…”
Section: Discussionmentioning
confidence: 99%